DEVELOPMENT OF A PHYSICAL ACTIVITY PROGRAM USING TRADITIONAL MEDICINE METHODS FOR POSTMENOPAUSAL WOMEN WITH ARTERIAL HYPERTENSION (Novateur Publications, 2024)
Rehabilitation is the restoration of health, functional status and work capacity that have been impaired as a result of diseases, injuries or physical, chemical and social factors. The goal of rehabilitation is to effectively and early return sick and disabled people to household and work processes, to society; restoration of personal characteristics of a person. The World Health Organization (WHO) defines rehabilitation as follows: "Rehabilitation is a set of activities aimed at helping people with functional impairments as a result of illness, injury and birth defects to get used to new conditions of life in the society in which they live." The term rehabilitation is derived from the Latin word habilis - "ability", rehabilis - "restoration of ability".Rehabilitation is a process aimed at providing comprehensive assistance to patients and disabled persons in order to achieve maximum physical, mental, professional, social and economic fulfillment in this disease.